Earthquake in the early morning - Osborne, Mary Pope.; Murdocca, Sal (2001)
The magic tree house takes Jack and Annie to San Francisco in 1906, in time for them to experience one of the biggest earthquakes the United States had ever known.
"Stepping stone."
Ages 6-10
Keywords: Earthquakes -- California -- San Francisco -- Juvenile fiction; Children's historical fiction; San Francisco (Calif.) -- Juvenile fiction; Time-travel fiction; Juvenile works; Time-travel fiction; Historical fiction; Children's fiction